CONSULTATION-LIAISON PSYCHIATRIC NURSING: AN ANALYSIS OF SCIENTFIC OUTPUT - Lídia Neusa de Freitas Glanzmann; Vanessa Pellegrino Toledo (Universidade Federal do Paraná, 2012)
This integrative literature review aimed to analyze what was published in scientific periodicals on the subject of consultation-liaison psychiatric nursing, focussing with a database of indexing, periodical, year of publication, methodological delineation and topic addressed. The article search was done with the PubMed, MEDLINE and LILACS databases, using the descriptor consultation-liaison psychiatric nursing and publication in the period 1999 - 2010. Ten articles were selected - the analysis permitted the identification that 50% of these were indexed in PubMed, 20% were found in the periodical Archives of Psychiatric Nursing, 20% in the International Journal of Mental Health Nursing and 20% in Perspectives in Psychiatric Care. The majority of publications were from 2008; 40% were qualitative or ethnographic studies. The most prevalent topics were application of consultation-liaison psychiatric nursing in patients and the opinion of nurses. The results show the necessity for more studies on the topic in Brazil and elsewhere in the world.